Method of reliability coefficients with adjustable values for steel structures design - V. V. Nadolski (Vestnik MGSU)
Introduction. The method of reliability coefficients with fixed values (declared in regulatory documents) is used as a basic method of limit state verification. However, there is a more general formulation of the semi-probabilistic method, within which the specificity of the design (e.g. information on the variability of actual dimensions, material properties, etc.) and the specificity of the location (e.g. information about climatic loads) can be taken into account more accurately. This method is referred to as the modified (adjustable) partial factor method.Materials and methods. The paper is aimed at the development of the method of reliability coefficients with adjustable values for the design of steel structures and the scientific justification of the parameters of this method. The methodological formulation of this method is based on determining the design values of the basic variables based on the distribution function for a given quantile. In this case, the quantile of the distribution is calculated using the sensitivity coefficients of the basic variables of the first-order reliability method and the target value of the reliability index.Results. The study describes in a general formulation a method of reliability coefficients with adjustable values for the design of steel structures, which allows explicitly taking into account the target reliability level and variability of the basic variables. In the course of the study, the scientific substantiation of the sensitivity coefficients of the basic variables based on the first-order reliability method was performed and instructions on the purpose of probabilistic models of random variables were presented.Conclusions. The analysis of the generalized function of the limiting state of the steel element by the probabilistic method showed that the sensitivity coefficients change significantly with the change in the loading parameter (characterizing the ratio of variable loads to the total), while it changes slightly depending on the type of variable load itself. Sensitivity coefficients can be assumed based on graphs or simplified dependencies presented in this study. Conservatively, the sensitivity coefficient values for the bearing capacity of the steel element can be assumed to be 0.6, for constant loading –0.4 and for variable loading –0.9.